Automatic Speech Recognition for Wireless Mobile Devices. - Rose, Richard C.; Parthasarathy, Sarangarajan (Tutorial Day at ICSLP 2002, 2002)
This tutorial will cover topics in automatic speech recognition (ASR) that are specific to the implementation of ASR systems on wireless mobile devices. Emphasis will be placed on algorithms and architectures that relate to ASR in the context of the mobile devices themselves, the environments they are used in, the networks they are connected to, and the target applications they support. The tutorial will have two major parts. The first part will consist of a survey of existing mobile ASR applications, architectures, and supporting technology. The second part will present algorithms that have been developed to make ASR systems more robust, more efficient, and more flexible for mobile applications.